Study of The Addition of Palm Shall Ash on Increasing Compressive Strength of Paving Block - Muhammad Rizki Harahap (Riviera Publishing, 2025)
Increasing development, the demand for building materials such as paving blocks is also increasing. With the many variations offered, the material for making paving blocks is not just a mixture of cement and sand. Crushed stone or gravel or other additives can also be used. In this study, palm shell ash was chosen as an additional material in making paving blocks, in order to increase the compressive strength of the paving blocks. This study was conducted by making 48 test specimens, then testing the compressive strength after the test specimens were soaked according to the predetermined planned age. This study refers to the implementation method of SNI 03-0691-1996 concerning concrete bricks (paving blocks). To obtain the optimal composition, various palm shell ash was added. Compressive strength testing was carried out when the test specimens reached the planned age. The results of the compressive strength test that had been carried out, it was found that the optimal addition of palm shell ash occurred at an addition of 8% at a soaking age of 28 days. So by referring to the regulations, concrete bricks (paving blocks) are included in the class C/IIIa quality category.